Konsep Mar’atun Salihah dan Implementasinya pada Mahasantri Ma’had al-Jami’ah - Alami, Syifaul; Zalida, Wardhia; Najwa, Alilah (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2023)
Being a woman is a natural thing that must be appreciated, because Islam highly upholds the rights and dignity of women. However, being a woman can be a disaster or a blessing, because women can be the key to heaven but can also be an extraordinary trial if we ignore our obligations as women in Islam. The purpose of this study is to explain the concept of mar'ah sholihah in Islam and find its implementation in students in the current era. To become a pious woman requires knowledge and a strategy and deep sincerity. Women in Islam have special virtues and positions. Position as a creation of Allah, child, wife, and even a mother. The method used is descriptive qualitative, namely describing the concept of mar'ah salihah and analyzing its implementation in students of the Ma'had al-Jami'ah. This study produces findings regarding the main concept of mar'ah sholihah, namely loyalty, obedience, and responsibility of women in carrying out religious orders